Análisis para la Implementación de un Servidor de servicios para la Unidad de Gestión Documental y Archivo de la Universidad Técnica de Babahoyo. - Moran Morales, Giancarlo Geovanny (2023)
There are many organizations that still manage the documentation by means of email and clouds (Clouds) created at the moment, this not only favors the loss of time and productivity, but also causes the information to be lost and unreliable, because it does not exist control over updated and sent documents with the proliferation of folders in emails and in the clouds. As what happens in the Faculty of Food Science and Engineering, as in the other Faculties that are part of the Technical University of Ambato, a large amount of information is generated, which circulates among the different departments that they have, it is for this reason, the sending and receiving of the different documents is done physically. The same ones that after meeting various requirements and going through various processes are approved or rejected, these processes are currently carried out manually, which leads to different deficiencies when continuing the processes, which is why it has been seen the need to automate the aforementioned processes to improve significantly in various aspects such as: Saving paper, avoiding the loss of important documents, streamlining processes and especially in their execution and monitoring. One of the problems is the huge volumes of documents, which over the years become economically unsustainable and eventually deteriorate due to the end of the useful life of the paper from which they were printed. One of the problems in his research was that since there is no adequate management of the information, which does not allow for an organized structure, which makes it difficult to access the particular aspects with which the organization is formed, such as: size, type of activity, capital, number of employees, optimization and automation of processes, communications, information management and technological infrastructure; This also means that the budgets for both creation and operation are manageable by the different companies, in order to plan and manage the information that is generated and circulates within the organizations. According to the internal regulations for document management and the Archive of the University of the Arts, those responsible for reception and document managers are in charge of the digitization process in each unit; This entails a series of steps combined with archival techniques for dematerialization that will guarantee the fidelity and completeness of the information that rests in the institution. Therefore, in this case study, the Implementation of a Service Server for the Document and Archive Management Unit of the Technical University of Babahoyo will be analyzed. As a solution, it is expected to use a server for the optimal functioning of the management systems, since that the information of the departments must be well protected, by this we mean that each unit will use the information in its management period and once it has completed its process, it will be sent to the general archive where it will be digitized and uploaded to the service server of the Document Management and Archive Unit. Once its management time has expired, it will be sent to the expungement and all the information will be available on the servers and will be used by the institution.